2020
DOI: 10.1177/0735633120929622
|View full text |Cite
|
Sign up to set email alerts
|

A ChatBot for Learning Chinese: Learning Achievement and Technology Acceptance

Abstract: ChatBot has potential as a language learning tool, especially for learning Chinese vocabulary. This study aimed to investigate the impact of using a newly developed ChatBot to learn Chinese vocabulary by comparing how it works in different learning environments and to explore the ChatBot with reference to the Technology Acceptance Model (TAM). This study was conducted with 58 students divided into two independent groups. The control group used ChatBot in a one-on-many classroom. The experimental group applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
102
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 47 publications
(65 reference statements)
17
102
0
2
Order By: Relevance
“…According to the related literature, since there were no teaching applications related to chatbots in science courses, the results obtained from this study were discussed by comparing them with the results of chatbot applications used in other courses, e-learning, mobile learning, and augmented reality. According to the literature, the chatbot developed for students to learn languages significantly improved the students’ learning success, and the results were better than what has been achieved in the classroom thanks to its ability to provide an individualized environment (Chen et al, 2020 ). In another study conducted to teach programming, a positive significant difference was observed in the germane load and sub-cognitive layer outputs of students using chatbots (Abbasi et al, 2019 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the related literature, since there were no teaching applications related to chatbots in science courses, the results obtained from this study were discussed by comparing them with the results of chatbot applications used in other courses, e-learning, mobile learning, and augmented reality. According to the literature, the chatbot developed for students to learn languages significantly improved the students’ learning success, and the results were better than what has been achieved in the classroom thanks to its ability to provide an individualized environment (Chen et al, 2020 ). In another study conducted to teach programming, a positive significant difference was observed in the germane load and sub-cognitive layer outputs of students using chatbots (Abbasi et al, 2019 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…According to Winkler and Söllner ( 2018 ), chatbots, have the potential to compensate for inadequate individual support from instructors for a variety of reasons, which include enabling the student to progress at their own pace, increasing the quality of the learning process and providing individual solution that can be applied proactively to increase learning outcomes. Chatbots that support students individually are spreading rapidly in the field of education (Arruda et al, 2019 ; Chen et al, 2020 ; Haller et al, 2005 ; Nghi et al, 2019 ). Moreover, Grudin and Jacques ( 2019 ) state that chatbots are one appropriate learning method for students to repeat their knowledge of previous topics and can be used to collect feedback about a course.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smutny and Schreiberova ( 2020 ), Wang et al ( 2021 ), and Winkler and Söllner ( 2018 ) added that the current domain of research in educational chatbots (EC) has been focusing on language learning (Vázquez-Cano et al, 2021 ), economics, medical education, and programming courses. Henceforth, it is undeniable that the role of EC, while not been widely explored outside these contexts (Schmulian & Coetzee, 2019 ; Smutny & Schreiberova, 2020 ) due to being in the introductory stages (Chen et al, 2020 ), are also constrained with limited pedagogical examples in the educational context (Stathakarou et al, 2020 ). Nevertheless, while this absence is inevitable, it also provides a potential for exploring innovations in educational technology across disciplines (Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The technology acceptance model has been successfully applied in several chatbot studies: its influence on behavioural intention (Rese, Ganster & Baier 2020), its impact on chatbots enhancing job performance in Indonesia's hotel industry (Gunawan, Putri & Meidia 2020) and its influence on chatbots' effectiveness in a learning environment in China (Chen, Widarso & Sutrisno 2020). Notwithstanding, no evidence in current literature could be found of studies investigating all the TAM's antecedence (PEOU, PU, PP) and their direct influence on chatbot experiences.…”
Section: Introductionmentioning
confidence: 99%